Attitudes towards Singlish : voices of Singaporeans overseas - Lee, Elsie Shu Ying (2019)
This study explores the attitudes of Singaporean undergraduate students living overseas towards the colloquial variety of English in Singapore, also known as Singlish. In Singapore, the government views Singlish negatively, and attempts to eliminate the usage of Singlish. By understanding the role that Singlish can play outside of Singapore, this study bridges a critical gap in research. Data consisting eight semi-structured interviews is collected from the participants. The results are analyzed by applying qualitative data analysis and the findings are presented thematically using a theoretical framework incorporating cognitive, affective, and behavioural components of attitude (Baker, 1992; Garrett, 2010). The findings illustrate positive attitudes towards Singlish, as participants consider it a marker of national identity and a tool for non-Singaporeans to assimilate better in the Singaporean community. Not only that, the distinctiveness of Singlish allows them to recognize and connect with other Singaporeans abroad, serving as a marker of solidarity. However, the findings also show the negative cognitive attitudes of participants towards Singlish, especially in contexts involving non-Singaporeans. The findings suggest that positive attitudes towards Singlish are prevalent in private domains with fellow Singaporeans and these are discussed in relation to the implications that researching attitudes has for the acceptance of Singlish in Singapore.